Kompetensi Managerial Kepala Sekolah dalam Meningkatkan Kinerja Guru Di SMP Negeri 9 Purworejo - Siti Nurlaili Chasanah (LPPM IAINU Kebumen, 2020)
This study aims to: (1) identify and analyze the technical skills of school principals in improving teacher performance at SMP Negeri 9 Purworejo, (2) identify and analyze the human skills of school principals in improving teacher performance at SMP Negeri 9 Purworejo Regency, (3) find out and analyzing the conceptual skills of school principals in improving teacher performance at SMP Negeri 9 Purworejo. This study uses a qualitative approach with the main data source being humans and the research results in the form of words or statements that are in accordance with the actual situation. The research subjects were school principals and the informants were vice principals and teachers of SMP Negeri 9 Purworejo. Data collection techniques using interviews, observation and documentation. The validity of the data using data triangulation techniques. Data analysis using data collection techniques, data reduction, data presentation and drawing conclusions. The results of the study show: (1) The technical skills of the principal of SMP Negeri 9 Purworejo Regency in improving teacher performance have gone well. Technical ability is a skill in using knowledge, methods, techniques, and equipment to complete certain tasks. Technical skills include the application of knowledge about classroom management, the use of teaching methods, student evaluation techniques, techniques for making learning program units, techniques for managing educational facilities and infrastructure, as well as techniques for directing and coaching teachers in schools. (2) The human skills of the head of SMP Negeri 9 Purworejo Regency in improving teacher performance are going well. Human ability is the ability of school principals to work together, communicate with school personnel in order to create an atmosphere of mutual trust in school programs and can provide motivation to improve teacher performance. Manifested by providing motivation, opportunities for self-development, appreciation, family attitude, good communication, and in delegating tasks. (3) The conceptual skill of the principal of SMP Negeri 9 Purworejo Regency in improving teacher performance has gone well. Conceptual ability in the form of the skills of the school principal to determine strategies, plan, formulate policies, and decide what happens within the organization, including schools as educational institutions listed in the vision, mission and goals of the school, plans for school activities for the short and long term.